2008
DOI: 10.1051/0004-6361:20079103
|View full text |Cite
|
Sign up to set email alerts
|

LoCuSS: comparison of observed X-ray and lensing galaxy cluster scaling relations with simulations

Abstract: The Local Cluster Substructure Survey (LoCuSS, Smith et al.) is a systematic multi-wavelength survey of more than 100 X-ray luminous galaxy clusters in the redshift range 0.14−0.3 selected from the ROSAT All Sky Survey. We used data on 37 LoCuSS clusters from the XMM-Newton archive to investigate the global scaling relations of galaxy clusters. The scaling relations based solely on the X-ray data (and L−M) obey empirical self-similarity and reveal no additional evolution beyond the large-scale structure growt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
235
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(272 citation statements)
references
References 103 publications
(258 reference statements)
36
235
1
Order By: Relevance
“…Mahdavi et al (2012) found that the scatter for clusters with low central entropies is particularly low, suggesting that the gas fractions vary very little for such clusters. Zhang et al (2008) found a lower gas mass in low mass systems than expected from a purely gravitational scenario, implying a steepening with respect to the prediction of the self-similar scenario.…”
Section: Thementioning
confidence: 57%
“…Mahdavi et al (2012) found that the scatter for clusters with low central entropies is particularly low, suggesting that the gas fractions vary very little for such clusters. Zhang et al (2008) found a lower gas mass in low mass systems than expected from a purely gravitational scenario, implying a steepening with respect to the prediction of the self-similar scenario.…”
Section: Thementioning
confidence: 57%
“…On the other hand, our masses are mostly calculated with double β-models, taking into account the temperature gradients. This is the same procedure as applied for the LoCuSS clusters (Zhang et al 2008), which we also include in the plots for comparison.…”
Section: Note On Model Choicementioning
confidence: 99%
“…The total gravitational mass of a cluster, consisting of both baryonic matter and dark matter, is tightly correlated with observable quantities such as temperature and luminosity, and relations between these have been studied extensively with both observational and computational techniques (e.g., Allen et al 2001;Finoguenov et al 2001;Reiprich & Böhringer 2002;Borgani et al 2004;Stanek et al 2006;Nagai et al 2007a,b;Rykoff et al 2008;Hartley et al 2008;Zhang et al 2008;Lopes et al 2009;Vikhlinin et al 2009;Ettori et al 2010;Leauthaud et al 2010;Mantz et al 2010;Plagge et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the low redshift Universe, weak lensing (WL) based mass measurements applied to sizable cluster samples have established massobservable relations with significantly improved accuracy (e.g. Reyes et al 2008;Zhang et al 2008;Marrone et al 2009). First weak lensing constraints on the evolution of scaling relations for X-ray groups are now available (e.g.…”
Section: Introductionmentioning
confidence: 99%